How to Overcome Anabolic Resistance in Dialysis-Treated Patients? - Garibotto, Giacomo; Saio, Michela; Aimasso, Francesca; Russo, Elisa; Picciotto, Daniela; Viazzi, Francesca; Verzola, Daniela; Laudon, Alessandro; Esposito, Pasquale; Brunori, Giuliano (Frontiers in Nutrition, 2021)
A current hypothesis is that dialysis-treated patients are “anabolic resistant” i. e., their muscle protein synthesis (MPS) response to anabolic stimuli is blunted, an effect which leads to muscle wasting and poor physical performance in aging and in several chronic diseases. The importance of maintaining muscle mass and MPS is often neglected in dialysis-treated patients; better than to describe mechanisms leading to energy-protein wasting, the aim of this narrative review is to suggest possible strategies to overcome anabolic resistance in this patient's category. Food intake, in particular dietary protein, and physical activity, are the two major anabolic stimuli. Unfortunately, dialysis patients are often aged and have a sedentary behavior, all conditions which per se may induce a state of “anabolic resistance.” In addition, patients on dialysis are exposed to amino acid or protein deprivation during the dialysis sessions. Unfortunately, the optimal amount and formula of protein/amino acid composition in supplements to maximixe MPS is still unknown in dialysis patients. In young healthy subjects, 20 g whey protein maximally stimulate MPS. However, recent observations suggest that dialysis patients need greater amounts of proteins than healthy subjects to maximally stimulate MPS. Since unneccesary amounts of amino acids could stimulate ureagenesis, toxins and acid production, it is urgent to obtain information on the optimal dose of proteins or amino acids/ketoacids to maximize MPS in this patients' population. In the meantime, the issue of maintaining muscle mass and function in dialysis-treated CKD patients needs not to be overlooked by the kidney community.